Highly Efficient Oxygen Evolution by a Thermocatalytic Process Cascaded Electrocatalysis Over Sulfur‐Treated Fe‐Based Metal–Organic‐Frameworks. Issue 16 (9th March 2020) - Feng, Kun; Zhang, Duo; Liu, Fangfang; Li, Hui; Xu, Jiabin; Xia, Yujian; Li, Youyong; Lin, Haiping; Wang, Shuao; Shao, Mingwang; Kang, Zhenhui; Zhong, Jun
Abstract: The oxygen evolution reaction (OER) is a bottleneck process for water splitting and finding highly efficient, durable, low‐cost, and earth‐abundant electrocatalysts is still a major challenge. Here a sulfur‐treated Fe‐based metal–organic‐framework is reported as a promising electrocatalyst for the OER, which shows a low overpotential of 218 mV at the current density of 10 mA cm −2 and exhibits a very low Tafel slope of 36.2 mV dec −1 at room temperature. It can work on high current densities of 500 and 1000 mA cm −2 at low overpotentials of 298 and 330 mV, respectively, by keeping 97% of its initial activity after 100 h. Notably, it can achieve 1000 mA cm −2 at 296 mV with a good stability at 50 °C, fully fitting the requirements for large‐scale industrial water electrolysis. The high catalytic performance can be attributed to the thermocatalytic processes of H + capture by –SO3 groups from *OH or *OOH species, which cascades to the electrocatalytic pathway and then significantly reduces the OER overpotentials. Abstract : Sulfur‐treated Fe‐based metal–organic‐framework can work as an efficient oxygen evolution reaction (OER) catalyst, which achieves 1000 mA cm −2 at a low overpotential of 296 mV with a good stability for 100 h. In situ X‐ray absorption spectroscopy (XAS) experiments and density‐functional theory (DFT) calculations reveal that the excellent OER performance can be attributed to the cascaded thermocatalytic processes with the insertion of S‐based groups in metal–organic‐frameworks (MOFs).